(untitled) (The Journal of Sindhuli Multiple Campus, 2026)
Sustainable road construction plays an indispensable role in mitigating environmental degradation that could be generated due to infrastructure projects nonetheless a thorough evaluation of these eulogized practices’ effectiveness is non-negotiable. This study investigates the environmental impacts of sustainable road construction practices, with a focus on community-driven approaches in Nepal that involve participatory planning and local stakeholder engagements. The research has systematically reviewed peer-reviewed literature accessible in databases such as Science Direct, Scopus, and Google Scholar, focusing on studies that address the environmental effects and community involvement in sustainable road construction. The findings reveal that community-driven approaches, if duly adopted, significantly reduce environmental impacts, particularly through the incorporation of recycled materials with participatory decision-making processes. Adoption of PRISMA study methodology regarding incorporation of recycled materials into operations and including them in decision-making process values much in this course. Factors such as stakeholder engagement, local regulations, and sustainability principles are detected to have strongly influenced expected outcomes. This paper, hence, emphasizes the possibility for alleviating/limiting the environmental damage due to road construction through enhanced community engagements. As the effectiveness of these approaches varies depending on location and socio-economic contexts, the follow-up of this research needs a focus on gaining a deeper understanding of these approaches and comparing their effectiveness across different geographic and socioeconomic settings.